Penerapan Permainan Tradisional Petak Umpet untuk Mengembangkan Kecerdasan Kinestatik Anak Usia 5-6 Tahun - Ayu Anggreni, Made; Nabilatun Nabighoh, Wahyun (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
Introduction: Nowadays, the parents are busy with their work, and Parentsintroduce many children to gadgets as play tools for children. The negative impactof children being passive and their development is hampered, especially on thechild's kinesthetic development is very low. Objective: The purpose of this studyprevent problems of early childhood education, by engaging in games directly thatencourage children to actively move through traditional games as a type of gamethat stimulates children to move actively. Method: The research method isquantitative with a purposive sample, which is based on the characteristics of thepopulation that have been known previously. Collecting data using tests throughobservation, observation, and documentation instruments which are thenanalyzed using t-test analysis. The experimental design used is the One Group Pretest-Post test. Result: The results obtained from the average pre-test are 5.18which are classified as children's kinesthetic intelligence abilities that have notdeveloped, and the results of the post-tests are 22.9 which show the children'skinesthetic intelligence abilities are very well developed. The results of thedifferent t-test (t-test) obtained a value of 63.46 with a significance level of 0.05(p>0.05): 63.46>1.72 and with a significance level of 0.01 (p>0.01): 63,46>2.52.So H0 is rejected and H1 is accepted. The traditional game petak umpet can be saidto have an effect on the kinesthetic intelligence of children at TKM NU 25 NurulHikmah Gresik. The traditional game petak umpet to relieve stress in children,children's bodies are healthy and affordable because they are cheap and anyonecan play.